INFLUENCE OF ABIOTIC STRESS FACTORS ON THE HYDRATION OF PLANT TISSUES OF SEDUM HYBRIDUM L. (AIZOPSIS HYBRIDA (L.) GRULICH) - Terletskaya, N.V.; Kobylina, T.N.; Kenzhebayeva, Zh.A. (Eurasian Journal of Applied Biotechnology, 2021)
Genus Sedum (family Crassulaceae) - succulents adapted to lack of moisture. Morphophysiological reactions of immature Sedum hybridum L. (Aizopsis hybrida (L.) Grulich) plants to stressful conditions of water scarcity, salinization and low positive temperatures are described. The high resistance of plants to the studied stress effects is shown. The tendency of the dynamics of the highest moisture loss by plants of the control group and the lowest by plants cultivated at PEG–6000 at a concentration of 200 mmol/l was noted, which indicates the adaptive effect of this level of osmotic stress on Sedum hybridum plants. To obtain a completely dry Sedum hybridum mass for various physiological experiments, it is necessary to maintain the plant material at a temperature of 105⸰ C, with at least 40 hours.